ANALISIS USAHATANI SAYURAN ORGANIK DI CV. RAHAYU DESA SIDERA KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Rifandi Rifandi; Marhawati M; Dafina Howara (Universitas Tadulako, 2022)
CV. Rahayu is an organic vegetable business actor located in Sigi District. To keep getting profits the company must improve efficiency, especially to minimize production costs. Determination of price strategy and sales volume as a component of determining the company's profit is very important in marketing, thus this business can maximize profits. This study aims to determine the cost structure of the organic vegetable business in CV. Rahayu and to determine the level of profitability of the organic vegetable business in CV. Grace. The research was carried out at CV. Rahayu, which is located in Bulupountu Jaya Hamlet, Sidera Village, Sigi Biromaru District, Sigi Regency in December 2020. The determination of respondents was carried out purposively. This study uses data analysis, namely cost structure analysis, revenue analysis, income analysis and business feasibility. Based on the results of the study, the average amount of organic vegetable production produced by CV. Rahayu amounted to 2,687 pcs at a price of Rp. 10,000/pcs so that the revenue was Rp. 26,870,000. The average production costs incurred by CV. Rahayu Rp 12,174,019. So that the average income earned is Rp. 14,695,981/year with an R/C value of 2.21, which means that the organic vegetable business is feasible.